Phase bias estimation for multi‐channel HRWS SAR based on Doppler spectrum optimisation. Issue 21 (1st October 2016) - Wang, Zhibin; Liu, Yanyang; Li, Zhenfang; Xu, Gang; Chen, Junli
Abstract : By applying digital beam‐forming (DBF) technique, the along‐track multi‐channel synthetic aperture radar (SAR) system can simultaneously achieve high‐resolution and wide‐swath (HRWS) imaging. However, the presence of unavoidable phase biases tends to degrade the DBF performance. To address this issue, a novel phase bias estimation algorithm based on Doppler spectrum optimisation is proposed. By exploiting the fact that phase bias would cause Doppler spectrum broadened, the phase biases can be successfully estimated by maximising a sharpness optimisation of the Doppler spectrum. The effectiveness of the algorithm is validated by experimental result carried out on the SAR data collected by an air‐borne multi‐channel system.